Plants’ molecular behavior to heavy metals: from criticality to toxicity - El-Sappah, Ahmed H.; Zhu, Yumin; Huang, Qiulan; Chen, Bo; Soaud, Salma A.; Abd Elhamid, Mohamed A.; Yan, Kuan; Li, Jia; El-Tarabily, Khaled A. (Frontiers in Plant Science, 2024)
The contamination of soil and water with high levels of heavy metals (HMs) has emerged as a significant obstacle to agricultural productivity and overall crop quality. Certain HMs, although serving as essential micronutrients, are required in smaller quantities for plant growth. However, when present in higher concentrations, they become very toxic. Several studies have shown that to balance out the harmful effects of HMs, complex systems are needed at the molecular, physiological, biochemical, cellular, tissue, and whole plant levels. This could lead to more crops being grown. Our review focused on HMs' resources, occurrences, and agricultural implications. This review will also look at how plants react to HMs and how they affect seed performance, as well as the benefits that HMs provide for plants. Furthermore, the review examines HMs transport genes in plants and their molecular, biochemical, and metabolic responses to HMs. We have also examined the obstacles and potential for HMs in plants and their management strategies.